2010
DOI: 10.1097/brs.0b013e3181fd591f
|View full text |Cite
|
Sign up to set email alerts
|

Complications in Spinal Deformity Surgery

Abstract: Mundane events can derail a perfectly executed surgical undertaking. Attention to detail, team work, close monitoring, and checklist type focus will help to improve, focus, and avoid these preventable complications that have nothing to do with direct surgical skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…In 2010 Carl et al [ 3 ] presented a study of 700 spine cases treated surgically and identified a 14% incidence rate of perioperative adverse events, which resulted in a final 3.2% complication rate.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010 Carl et al [ 3 ] presented a study of 700 spine cases treated surgically and identified a 14% incidence rate of perioperative adverse events, which resulted in a final 3.2% complication rate.…”
Section: Introductionmentioning
confidence: 99%
“…2C). EBL was not statistically different between the two groups, which could be explained by the presence of nonmodifiable factors contributing majorly to EBL, including age and comorbidities, and the presence of underlying bleeding disorders 36 …”
Section: Discussionmentioning
confidence: 78%
“…EBL was not statistically different between the two groups, which could be explained by the presence of nonmodifiable factors contributing majorly to EBL, including age and comorbidities, and the presence of underlying bleeding disorders. 36 In addition, patients in the staged group had a higher rate of overall complications and especially VTE. Having a staged spinal fusion surgery increased the risk of VTE (odds ratio = 4) when compared with same-day surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Traditional open surgery had high complication incidence rate from 20% to 80%, such as pain, swelling of incision, large amount of blood loss, and even death. [ 8 14 53 54 55 ] Several factors were correlated strongly with the incidence of complications, such as age, number of levels operated, and time of operation. [ 20 56 ] MISS could avoid some disadvantages of traditional procedure; it also had certain complications compared to open surgery.…”
Section: Omplications Of M Inimally mentioning
confidence: 99%